The Effect of Chromium on Human-Health: A Review - Pokhrel, Ganga Raj; Pokhre, Galaxy (BMC Journal of Scientific Research, 2022)
This review presents the health effects of chromium on the living organism based on previous studies. Chromium (Cr) belongs to the d-block element in the modern periodic table. Chromium has a wide range of oxidation states ranging from -2 to +6. Chromium mostly exists in the environment as trivalent (Cr3+) and hexavalent (Cr6+) states. Both trivalent and hexavalent states of chromiums are derived from the industrial effluents. Ingestion, dermal contact, and inhalation are the most common routes through which chromium enters the human body. Ion chromatography inductively coupled plasmamass spectrometry (IC-ICP-MS) is mostly used for the speciation analysis of metals. Hexavalent chromium is highly soluble and mobile in alkaline and slightly acidic soils, whereas trivalent chromium is less soluble, adheres to the coarse material on the soil, and precipitates as Cr(III) hydroxide. Hexavalent chromium is more detrimental as compared to trivalent chromium. The detrimental effects of chromium are bronchial asthma, lung cancer, nasal ulcers, skin allergies, carcinogenicity, and genotoxicity. To protect from these adverse effects, WHO has suggested a provisional guideline value of chromium as 0.05 mg/L until further information is available and revalued.